Evaluation of the near fundamental frequency oscillation in the off-shore wind farms based on the elastic energy flow - Han, Jiangbei; Liu, Chengxi; Shang, Lei; Dong, Xuzhu (International journal of electrical power & energy systems, 2025)
•The elastic energy flows at multiple dimensional freedom are developed to describe the energy exchange and dissipation during the oscillation.•A dissipated gradient criterion is developed to identifies the security regions of the oscillatory system.•The elastic energy flows reveal distinct mechanisms between NFFOs and SSOs by evaluating the energy dissipation at different frequencies. It is known that the dynamics of inverter-based resources (IBRs) may interact at non-fundamental frequencies. This paper proposes an elastic energy flow (EEF) method to investigate the distinct mechanisms of near-fundamental frequency oscillation (NFFO)—where the oscillation frequency is within ± 10 Hz of the fundamental frequency—and conventional subsynchronous oscillation (SSO) between the permanent magnet synchronous generator (PMSG)-based wind farm and the modular multilevel converter high-voltage direct current (MMC-HVDC) station. The EEF method not only identifies the security regions of the oscillatory system during SSO and NFFO by establishing a dissipated gradient criterion but also provides a parameter adjustment scheme for mitigating oscillations at different frequencies. As a representative case study, the EEF is applied to elucidate the distinct mechanisms of NFFO and conventional SSO in offshore wind farms based on PMSGs integrated with a MMC-HVDC station. Analytical and simulation results demonstrate that the EEF enables the determination of security regions and optimal control parameters required for mitigating NFFO and conventional SSO, respectively.